Validation of an animal welfare protocol on dairy goat farms (FAVE Sección Ciencias Veterinarias, 2025)
The purpose was to validate animal welfare indicators through an animal welfare assessment protocol in goat milkfarms under different production systems in the northwest (NOA) of Argentina. The study included 6 extensive farms and 5semi-extensive farms with daytime grazing and nighttime confinement and 1 with total confinement, located in the regions ofarid canyon and valleys (n=7, QyVA) and temperate valleys and rain forest (n=5, VTyY). The protocol was divided into two parts,one based on the observation of the environment conditions, nutritional, sanitary and milking management, animal behaviorand human-animal relationship. The second was based on the inspection of 20 ±5 goats in milking, recording the prevalence ofbody condition, cleanliness degree,clinical signs and hoof trimming and dehorning. Each parameter received a partial score tobe summed to obtain the final total score, where those parameters observed directly by the evaluators were emphasized over thoserecorded through the producer's report. The protocol was feasible since the implementation time was less than 2 hours and thecosts were low. The final average score of the farms was 64.4±17.4%, over the final optimum score, reaching the maximum in the2category of prevalence of individual clinical signs (87.2%) and the minimum in social interaction and contributions to wellbeing (28.1%). When analyzing by category of well-being, differences were only found between the extensive and semi-extensivesystems regarding environment conditions and comfort (X24.3; p< 0.04) and environment and hygiene (X27.0; p< 0.008),where a greater number of semi-extensive systems exceeded the average score of the total farms compared to the extensive ones.Regarding the prevalence of clinical signs, a trend was observed (X23.08; p< 0.07) that a greater number of those flocks locatedin the QyVA region exceeded the average score compared to those located in the VTyY, which presented a higher prevalence ofFamacha scores 4 and 5 and lameness. It is concluded that the selected set of management and animal-based measures was ableto discriminate the welfare of goats between farms in different regions and productive systems of the NOA
Keywords: dairy goats; animal welfare; assessment protocol; Argentina Northwest